Faktor-Faktor yang Berhubungan dengan Motivasi Petani dalam Mempertahankan Lahan Pertanian Tanaman Padi (Studi Kasus: Kecamatan Palas, Kabupaten Lampung Selatan) - Valencia, Vera; Aprildahani, Baiq Rindang (Jurnal Perencanaan dan Pengembangan Kebijakan, 2024)
Palas District is the area that contributes the highest rice production in South Lampung Regency, but land conversion often occurs. This marked by decrease in the area of ​​rice fields and the amount of rice production during 2017-2022. The land conversion will have an impact on reducing the amount of rice production that can pose a threat to food security. Efforts to control land conversion should focused more on farmers because farmers are the first actors involved in exploiting agricultural land. The change of rice fields to other uses determined by farmer's decision, where this decision can driven by motivation originating from internal and external factors. Amid the high flow of agricultural land conversion in Kecamatan Palas, there are still farmers who maintain their agricultural land. Therefore, the purpose of this research is to determine the factors related to farmer’s motivation in maintaining rice farming land in Palas District. The approach used is quantitative deductive using cross tabulation analysis. The research results show that farmers' motivation to maintain agricultural land largely driven by factors originating from the farmers' own conditions.